A LANGUAGE AND SOCIAL CONTEXT IN THE SYMBOLS OF THE RITUAL REBO BUNTUNG - Diah Supatmiwati; Wiya Suktiningsih; Ni Ketut Sriwinarti; Ni Nyoman Widani; Sutarman (Kulturistik: Jurnal Ilmu Bahasa dan Budaya, 2023)
Lombok island is a piece of paradise rich in tradition and culture. The practiced tradition that still exists in Lombok is Rebo Bontong Tradition; it is especially practiced by the people around the coastal area of ​​Tanjung Menangis, Pringgabaya, East Lombok. In the present time, the development of modern technology has touched and influenced society, which has become a challenge for the community to maintain and preserve the existing values ​​or culture. The tradition of Rebo Bontong in practice in the past was different from what it is now. The previous tradition merely focused on worship without any entertainment elements in it; at the present, it is functioning as entertainment. Related to those notions, the problem arises are the current traditions and values of the Rebo Bontong ritual are eroded by the influence of modernization or are still the same. Therefore, this study aims to redefine the meaning of each value in the Rebo Bontong tradition as an effort to maintain the existence of traditional cultural meanings from generation to generation. This research is qualitative research using an ethnographic method approach that aims to study, describe, analyze and interpret the cultural patterns of an ethnic group in terms of behavior, beliefs, language, and shared views. This research was conducted at Ketapang Beach, Tanjung Menangis, Pringgabaya District, and East Lombok Regency. The results showed that the ritual symbolized the new meanings; they are (1) a symbol of intergenerational unity and (2) a symbol of environmental harmony and moral values as well as customs within the framework of religious culture. (3) Social symbols which are part of the social bond, social interaction media, and socialization media